Crystalline and amorphous structure of astrophysical ices - Strazzulla, G. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
The structure of water and other ices strongly depends on the temperature at which they formed, e.g., by vapor deposition. It is amorphous if ices are formed at low temperature (e.g., 10–30 K for water ice), or crystalline if the deposition temperature is higher (140–150 K). Ices have a “polycrystalline” structure at intermediate temperatures. The crystalline structure of ices can be damaged up to a complete amorphization by processes such as those due to energetic ion bombardment. Here I describe some experimental results obtained by ion irradiation of water and ammonia ices, two species particularly relevant in astrophysics. The results are discussed in the light of the relevance they have in astronomical environments where the actual structure of the ices depends on a competition between energetic processing that induce amorphization and thermal annealing that favors the tran-sition towards more ordered structures.